1997
DOI: 10.1073/pnas.94.26.14770
|View full text |Cite
|
Sign up to set email alerts
|

N -methyl- d -aspartate receptor activation and visual activity induce elongation factor-2 phosphorylation in amphibian tecta: A role for N -methyl- d -aspartate receptors in controlling protein synthesis

Abstract: N -methyl- d -aspartate receptor (NMDAR) activation has been implicated in forms of synaptic plasticity involving long-term changes in neuronal structure, function, or protein expression. Transcriptional alterations have been correlated with NMDAR-mediated synaptic plasticity, but the problem of rapidly targeting new proteins to particular synapses is unsolved. One potential solution is synapse-specific protein translation, which is suggested by dendritic localization of num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…For example, glutamate or NMDA treatment of cortical neurons in culture leads to a rapid and pronounced increase in eEF2 phosphorylation, and a decrease in translation rates in cell bodies and proximal (but not distal) cell processes (121). Activation of the NMDA receptor also leads to eEF2 phosphorylation, in tadpole tecta (122). It is tempting to speculate that mTOR could inhibit eEF2 phosphorylation in active synapses to locally derepress translation.…”
Section: How Might Tor Signaling Be Involved In Learning and Memory?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glutamate or NMDA treatment of cortical neurons in culture leads to a rapid and pronounced increase in eEF2 phosphorylation, and a decrease in translation rates in cell bodies and proximal (but not distal) cell processes (121). Activation of the NMDA receptor also leads to eEF2 phosphorylation, in tadpole tecta (122). It is tempting to speculate that mTOR could inhibit eEF2 phosphorylation in active synapses to locally derepress translation.…”
Section: How Might Tor Signaling Be Involved In Learning and Memory?mentioning
confidence: 99%
“…It is tempting to speculate that mTOR could inhibit eEF2 phosphorylation in active synapses to locally derepress translation. It has also been suggested that eEF2 phosphorylation could actually enhance the translation of specific mRNAs localized to dendrites by driving these mRNAs from untranslated ribonucleotide particles or small polysomes into larger polysomes (122)(123)(124)(125).…”
Section: How Might Tor Signaling Be Involved In Learning and Memory?mentioning
confidence: 99%
“…Other studies have indicated a possible inhibitory role of synaptic activity on translation. In adult frog tecta, activation of NMDA receptors and visual activity led to activation of calcium/calmodulindependent EF2 kinase, resulting in the phosphorylation of eEF2 at subsynaptic sites (Scheetz et al 1998). It is known that phosphorylation of eEF2 arrests translation elongation.…”
Section: Regulation Of Dendritic Protein Synthesismentioning
confidence: 99%
“…Recent studies showed that the eukaryotic translation elongation factor 2 (eEF2) is phosphorylated in response to N-methyl-D-aspartate (NMDA) receptor activation and visual activity in the intact tadpole tecta; phosphorylation of eEF2 occurs at the subsynaptic regions (Scheetz et al 1998). In eukaryotic cells, phosphorylation of eEF2 is associated with reduced protein synthesis, probably by halting ribosomal translocation (Narin & Palfrey 1996).…”
Section: Regulation Of Dendritic Protein Synthesismentioning
confidence: 99%
“…However, in neuronal tissue no receptor-mediated mechanism that up-regulates localized postsynaptic translation has been described. A receptor-mediated inhibition of protein synthesis in neurons has been described that involves N-methyl-D-aspartate-induced phosphorylation of eukaryotic elongation factor 2 (eEF-2) by activation of calcium͞calmodulin-dependent protein kinase III (EF-2 kinase) (21,22).…”
mentioning
confidence: 99%